2013
DOI: 10.1186/1750-1326-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Conformational templating of α-synuclein aggregates in neuronal-glial cultures

Abstract: BackgroundGenetic studies have established a causative role for α-synuclein (αS) in Parkinson’s disease (PD), and the presence of αS aggregates in the form of Lewy body (LB) and Lewy neurite (LN) protein inclusions are defining pathological features of PD. Recent data has established that extracellular αS aggregates can induce intracellular αS pathologies supporting the hypothesis that αS pathology can spread via a “prion-like” self-templating mechanism.ResultsHere we investigated the potential for conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 59 publications
6
70
4
Order By: Relevance
“…Previous experimental studies have provided evidence for in vivo prion-like spread of αS pathology (21-26); however, several findings here, and in other recent studies from our group, suggest that additional nonexclusive mechanisms inducing or promoting αS inclusion pathology formation should be considered (33,(51)(52)(53). Indeed, (i) the distribution of αS pathology in M83 Tg mice IM injected with various forms of αS was identical to that seen in untreated, aged M83 Tg mice, (ii) IM injection of a nonamyloidogenic form of αS (Δ71-82) induced CNS αS inclusion pathology, albeit less efficiently than fibrillar αS, and (iii) there were significant increases of both astrogliosis and microgliosis associated with the regions where abundant αS pathology was induced.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Previous experimental studies have provided evidence for in vivo prion-like spread of αS pathology (21-26); however, several findings here, and in other recent studies from our group, suggest that additional nonexclusive mechanisms inducing or promoting αS inclusion pathology formation should be considered (33,(51)(52)(53). Indeed, (i) the distribution of αS pathology in M83 Tg mice IM injected with various forms of αS was identical to that seen in untreated, aged M83 Tg mice, (ii) IM injection of a nonamyloidogenic form of αS (Δ71-82) induced CNS αS inclusion pathology, albeit less efficiently than fibrillar αS, and (iii) there were significant increases of both astrogliosis and microgliosis associated with the regions where abundant αS pathology was induced.…”
Section: Discussionmentioning
confidence: 44%
“…Under experimental native and physiological conditions, Δ71-82 αS is refractory to amyloid formation, and it does not promote or influence amyloid formation of full-length αS (32,33,36,37); however, under nonphysiological conditions (i.e., the presence of SDS), it can be artificially induced to form amyloid fibrils (54). At present, we cannot completely exclude the possibility that a small amount of soluble Δ71-82 αS may spontaneously form amyloid seeds in vivo.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to previous reports, we found that neurons exposed to aSyn aggregates develop S129 p-aSyn inclusions, displaying increased levels of insoluble aSyn (38,49). However, in contrast to other studies (39), overexpression of the cellular aSyn or expression of the human form was not required. The inclusions formed could be classified depending on their localization in the cell.…”
Section: Discussionmentioning
confidence: 47%
“…In neurons, astrocytes and mixed primary cells, sonicated A53T fibrils seeded 'flame-like inclusions', whereas small E46K fibrils prompted the formation of punctate roundshaped structures depending on the form of α-syn expressed. In addition, the inclusions could be transferred during passaging in a prion-like manner [19]. Further evidence for the prion-like seeding mechanism of α-syn has arisen from a variety of in vivo experimentation at the cellular, intercellular and tissue levels which has been strengthened by sporadic cases of transmission in mesencephalic transplants of PD patients.…”
Section: Introductionmentioning
confidence: 99%